BEBERAPA ASPEK GEOMETRIKA JALAN HUTAN DAN HUBUNGANNYA DENGAN EROSI TANAH - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1990)
A  study  on  the  forest road geometrics in  relation   to  the  process  of  soil  erosion  was  carried out  at four  logging companies in Kotawaringin Timur, Central  Kalimantan   in 1988. Road geometric aspects  measured  in the  field  are those related  to the  Universal Soil Loss Equation factors  such  as road openings, surfaces,  slopes,  ditches,  culverts,  cuts,  fills,diversion  ditches,  and  the  incidence   of  vegetation.The result  shows that  forest road geometrics are in the condition of  high potentials   for  soil erosion.  Factors  that caused  this  problem,  as  identified   in the  field,  are: long and steep slopes, wide ground  openings, and bare soil surfaces, in addition to the  originally  sensitive  to erosion  soil  type,  an.d hot  and  wet  weather.The concessionaires and  Indonesian Government  have  not  given  proper  attention  to  the  seriousness  of  this  soilerosion  yet.  Qualitatively  we know   that  the  erosion  level  is high  but  quantitatively  we  do not know  the value yet. Therefore, further study is necessary.